2020
DOI: 10.1038/s41477-019-0580-z
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental plasticity of lateral roots in response to asymmetric water availability

Abstract: Root branching is influenced by the soil environment and exhibits a high level of plasticity. We report that the radial positioning of emerging lateral roots is influenced by their hydrological environment during early developmental stages. New lateral root primordia have both a high degree of flexibility in terms of initiation and development angle towards the available water. Our observations reveal how the external hydrological environment regulates lateral root morphogenesis. Main textThe soil environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Root developmental plasticity results from a number of components, including a variable number of participating FC files, nonstereotypical pattern formation, and a flexible morphogenetic response to available water (13,14,34). In this study, we revealed an additional plasticity component related to the absence of a specific pattern and sequence of FC recruitment.…”
Section: Discussionmentioning
confidence: 61%
“…Root developmental plasticity results from a number of components, including a variable number of participating FC files, nonstereotypical pattern formation, and a flexible morphogenetic response to available water (13,14,34). In this study, we revealed an additional plasticity component related to the absence of a specific pattern and sequence of FC recruitment.…”
Section: Discussionmentioning
confidence: 61%
“…This was because biochar application facilitated the growth of many more lateral roots with smaller diameter in the rice plants ( Figure 8 ). This observation indicates that biochar application improved root architecture because the lateral roots are critical to allowing the plants to take up water and minerals effectively ( von Wangenheim et al, 2020 ). Auxin is required for lateral root formation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on approaches with high-speed acquisition rates and minimal photodamage to the biological sample, researchers collected long-term and in-depth data at subcellular resolution to probe the spatiotemporal pattern of the cellular landscape (Ovečka et al, 2018). A 3D rendering of the cellular landscape in the lateral root (LR) was captured for unmasking how the external hydrological environment regulates LR morphogenesis (von Wangenheim et al, 2020). In addition, LR morphogenesis was detected by application of LSFM, showing that the interaction with overlying tissues, rather than the precise pattern of cell division, is critical for LR primordia morphogenesis and optimizes the process of LR emergence (Lucas et al, 2013a).…”
Section: Spatiotemporal Pattern Of the Cellular Landscapementioning
confidence: 99%